2022
DOI: 10.23939/chcht16.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Phosphorus-Containing Pseudo-Poly(Amino Acid)sof Polyester Type Based on N-Derivatives of Glutaminic Acid

Abstract: Poly(phosphoeter)s (PPE)s are a class of polymers possessing a high chemical functionality and biodegradability. Novel, glutamic acid based poly(phosphoeter)s were synthesized by the Steglich reaction. The developed synthetic approach allows controlling the composition and the structure of PPEs, and therefore their physical and colloidal properties. The studies on solubilization and cytotoxicity in vitro proved the potential of PPEs for drug delivery applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The obtained molecule contains lipophilic and hydrophilic fragments, which exhibit amphiphilic properties. It has surfactant properties and the ability to form self-stabilized dispersions with a nanometric dispersed phase in aqueous and physiological solutions [ 25 , 26 ]. The presence of a phosphate group (in the hydrophilic fragment after hydrolysis of the ethoxy group) provides conjugates with molecules that exhibit base properties [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The obtained molecule contains lipophilic and hydrophilic fragments, which exhibit amphiphilic properties. It has surfactant properties and the ability to form self-stabilized dispersions with a nanometric dispersed phase in aqueous and physiological solutions [ 25 , 26 ]. The presence of a phosphate group (in the hydrophilic fragment after hydrolysis of the ethoxy group) provides conjugates with molecules that exhibit base properties [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…As shown in the results, newly created transporters of the polyphosphate ester type were able to bind and solubilize oxytetracycline. Studies have shown that polymers based on pseudo-polyamino acids, which are similar to polyphosphate ester-type nano transporters, penetrate cells and mitochondria [ 27 , 28 , 29 ]. Low-charged and amphiphilic properties facilitate membrane penetration by these compounds [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation